Detection of enterotoxigenic Escherichia coli in water by filter hybridization with three enterotoxin gene probes. - Echeverria, P (1982)
The DNA hybridization assay for genes encoding for Escherichia coli enterotoxins was used to examine water specimens in Thailand. In a reconstruction experiment, the DNA hybridization assay was 10(4) times more sensitive than testing random E. coli in the Y-1 adrenal and suckling mouse assays in identifying enterotoxigenic E. coli (ETEC) in water. Drinking and bathing water collected from 2 of 10 different homes of individuals with ETEC-associated diarrhea and 6% (5 of 78) and 11% (11 of 78) of drinking and bathing water samples collected from homes of individuals with diarrhea without ETEC infections, as well as 6% (5 of 77) and 8% (6 of 77) of drinking and bathing water collected from homes in which no inhabitants had diarrhea, were homologous with the DNA probes. Ten E. coli from each of the 31 water specimens which contained bacteria which were homologous with the DNA probes were tested in the Y-1 adrenal and suckling mouse assay. In only 2 of these 31 specimens could ETEC be identified with the standard assays. The DNA hybridization assay is a much more sensitive means of detecting organisms carrying genes coding for enterotoxin production than testing 10 individual colonies in the Y-1 adrenal and suckling mouse assays. This novel application of recombinant DNA technology provides a sensitive method of detecting organisms carrying genes coding for enterotoxin, and this method will be useful in defining the epidemiology of ETEC.